Study on Coal Spontaneous Combustion Characteristics under Methane-Containing Atmosphere. Issue 8 (3rd August 2019) - Ma, Li; Guo, Ruizhi; Gao, Yu; Ren, Lifeng; Wei, Gaoming; Li, Chaohua
ABSTRACT: To explore the effects of methane on the characteristics of coal spontaneous combustion, coal low-temperature oxidation and Fourier transform infrared spectroscopy experiments were conducted. The tested airflows had an oxygen–nitrogen ratio of 0.266, and methane concentrations of 0−3% by volume. Moreover, the coal oxidation characteristics and the various types and quantities of functional groups were investigated. The results show that CO/CO2 production and oxygen consumption rates were higher for coal samples under airflow atmospheres containing methane than for airflow atmospheres without methane. However, the apparent activation energy of coal samples in airflows containing methane was lower than for airflow atmosphere without methane. It is speculated that airflows with 1−3% methane concentrations have a positive impact on coal spontaneous combustion. This study used OMNIC and PeakFit v4.12 programs to analyze the effect of airflows containing methane on the functional groups of coal spontaneous combustion. The Pearson correlation coefficient method was introduced to analyze the relationship between the key functional groups and apparent activation energies of coal samples. The results indicated that the key functional groups of the coal samples below the critical temperature were methyl (−CH3 ) and methylene (−CH2 ). Above the critical temperature, aromatic C−H, methyl (−CH3 ), and methylene (−CH2 ) were the key functional groups. After reaching the cracking temperature, aromatic C−H and alkyl ether C−O−C became the key functional groups. With increasing methane concentration, aromatic C–H makes a negative contribution to coal spontaneous combustion, while methyl (−CH3 ) and methylene (−CH2 ) make positive contributions. The inhibition of alkyl ether C−O−C to coal spontaneous combustion is weakened, and the inhibition of aromatic ring C=C to coal spontaneous combustion is enhanced.